KEDUDUKAN WALI BAGI PEREMPUAN DALAM PERNIKAHAN : (Perbandingan antara Hukum Positif dan Fiqh) - wahyuni, sri wahyuni (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2022)
This paper discusses the position of guardian for women in marriage by making a comparison between positive law – in this case the Marriage Law – and the discourse on marriage guardians in fiqh as well as referring to the arguments and legal differences of opinion among the scholars of the schools of fiqh. In positive law in Indonesia - the Marriage Law - guardians or parents only play a role in being asked for approval when their children want to marry. Based specifically on this Marriage Law, the marriage contract does not have to be pronounced by the guardian. Thus, women can carry out their own marriage contract, with the approval of their guardian, because women are legal subjects who have perfect legal skills. Meanwhile, in fiqh, there are differences of opinion, namely that Hanafiyah scholars allow women to marry without the consent of their guardians, and women may marry themselves, because women who have reached puberty are considered to have perfect legal skills. Another opinion is that put forward by Jumhur Ulama that guardians can marry girls without their permission and guardians can marry widows with their permission. However, the marriage contract – for both girls and widows – still has to be pronounced by the guardian. The marriage contract pronounced by the woman herself is considered invalid.